Lear and Quijote, two wanderers on uneven paths - Relvas, Maria de Jesus Crespo (The Grove - Working Papers on English Studies, 2019)
King Lear of Britain and Don Quijote de la Mancha, both old and frail, are dwellers of two very different worlds and eras. The ways they were devised and shaped by William Shakespeare and Miguel de Cervantes generate nonetheless diverse similarities that emphatically expose crucial traits of the human nature.     The meaningful, more obvious dichotomies in the texts – such as Reality/Fantasy, Sight/Blindness, Truth/Falsehood, Loyalty/Treachery – frame the complexity of the protagonists and are metaphors of their antithetical features. On the other hand, their alienation, misapprehension and distortion of the surrounding realities turn them into wanderers on uneven, problematic paths, while their frail physical condition discloses a surface layer that encapsulates assertive individuals.This essay approaches Shakespeare’s and Cervantes’ texts by focusing on such aspects, as well as on the respective contextualisation. Each work constitutes a challenging exemplum of a unique, proficuous broad age that wisely amalgamated the old and the new: amidst a multitude of cultural traditions, King Lear primarily embodies the expansion of Tragedy, while Don Quijote de la Mancha primarily materialises the transition to a new stage of Modernity.Keywords: Lear; Quijote; dichotomies; alienation; tradition; innovation